Diversity of Leaf Stomatal Traits among Coffea canephora Pierre ex A. Froehner Genotypes - Danielly Dubberstein; Marcos Góes Oliveira; Elisa Mitsuko Aoyama; José Henrique Guilhen; Adésio Ferreira; Isabel Marques; José C. Ramalho; Fábio Luiz Partelli (Agronomy, 2021)
Leaf morpho-anatomical characteristics directly reflect photosynthetic performance and the ability to adapt to different environmental conditions. The study of biometric traits is essential for the selection of promising plant materials for breeding purposes. To identify new varieties of coffee plants with desirable traits for genetic improvement programs, this study investigated the variability of leaf morpho-anatomical traits in 43 genotypes of Coffea canephora (as the species under study is hypostomatous). Seven leaf characteristics were used: epidermal cell density (ECD), stomatal length (SL), stomatal width (SW), stomatal density (SD), stomatal size (SS), stomatal index (SI), and stomatal length/width. Morphological traits (plant height, internodal distance, and leaf area) and grain production were also assessed. The data analyzed multivariate analysis of variance grouped by the unweighted pair group the arithmetic mean hierarchical method, and data were also subjected to a Pearson linear correlation and principal component analyses (PCAs). The results showed wide morphological variability reflecting six morphological groups, which is relevant for the genetic divergence analysis and for breeding purposes, as the results have the potential to identify superior genotypes. Within the groups, genotypes were mainly separated by the number of epidermal cells and the number and size of the stomata, reflecting a high genetic heterogeneity within genotypes. Positive and negative correlations were found, with levels of significance ranging from weak to strong among the analyzed traits. The highest correlation levels were found for SL × SS, SW × SS, and SI × SD. In addition, the PCA indicated that plant height, distance between nodes, and leaf area were positively correlated and associated. The greater the number and width of stomata, the higher the rate of gas exchange. Both characteristics are favorable for the development and production of coffee plants, explaining the positive correlation observed in this study. These results emphasize the usefulness of trait evaluations for the identification and breeding of genotypes to compose new C. canephora cultivars suitable for changing environments.